Acculturation a personal journey across cultures - Berry, John W. 1939- (Elements in psychology and culture, 2019)
Acculturation is the process of group and individual changes in culture and behaviour that result from intercultural contact. These changes have been taking place forever, and continue at an increasing pace as more and more peoples of different cultures move, meet and interact. Variations in the meanings of the concept, and some systematic conceptualisations of it are presented. This is followed by a survey of empirical work with indigenous, immigrant and ethnocultural peoples around the globe that employed both ethnographic (qualitative) and psychological (quantitative) methods. This wide-ranging research has been undertaken in a quest for possible general principles (or universals) of acculturation. This Element concludes with a short evaluation of the field of acculturation; its past, present and future